Reaping the Benefits of Conservation Tillage: Implications of Increased Soil Organic Matter and Aggregation in Surface Soils - Kenna Rewcastle (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
In light of the US Department of Agriculture’s initiatives to reduce herbicide application on agricultural lands by 10% and increase soil carbon sequestration by 15%, the agriculture industry is in need of a cultivation practice that allows for more efficient herbicide application and fosters soil carbon accumulation. Our study presents a broad evaluation of the ability of conservation tillage techniques to meet the demands of this goal while maintaining high crop yields. We investigate the implications of increased organic matter and improved soil structure in conservation tillage soils for the protection and storage of soil carbon within stable microaggregates and the retention of herbicide chemicals in the bulk soil. To do so, we complete a soil respiration study to analyze carbon storage in different soil size fractions and design a novel column system to analyze herbicide transport through surface soils. The results of this preliminary study suggest that conservation tillage is a viable method of fulfilling the USDA’s initiatives to ensure the sustainability of the agriculture industry in the face of climate change.